Clinical and radiological study of single-level degenerative lumbar disc disease in Eastern India Medical College - Krishnendu Sardar; Md Salim Uz Zaman; Soumedhik Dey; Sumana Baidya (Asian Journal of Medical Sciences, 2025)
Background: Low back pain secondary to lumbar disc degenerative disease (LDDD) usually affects young to middle-aged persons. It presents as a sharp shooting type of pain, mild tingling sensation, and a dull ache. There are many risk factors associated with the LDDD, such as advancing age, smoking, and obesity. The annual incidence of prolapsed lumbar intervertebral disc is about 5–10%. Lumbar disc herniation is the pathological condition for which spinal surgery is most often performed. Treatment for lumbar disc herniation can be conservative or surgical, and which one is effective is always controversial. The purpose of conducting this study is to assess different clinical features, magnetic resonance imaging (MRI) characteristics, and postsurgical outcome of single-level lumbar disc disease.